IL-17A in gastric carcinogenesis: good or bad? - Li, Weidong; Huang, Xiaodong; Han, Xiaowen; Zhang, Jiayi; Gao, Lei; Chen, Hao (Frontiers in Immunology, 2024)
Cytokines, which are important to the tumor microenvironment (TME), play critical roles in tumor development, metastasis, and immune responses. Interleukin-17(IL-17) has emerged as a key biomarker in many malignancies; however, its precise involvement in gastric cancer is less fully understood. Elevated levels of IL-17 have been observed in stomach diseases such as Helicobacter pylori infection and autoimmune gastritis, indicating that a sustained Th17 response may precede the development of gastric cancer. While IL-17 is related to inflammatory processes that may lead to cancer, its specific influence on gastric cancer development and therapy needs to be completely understood. Specifically, the release of IL-17A by diverse immune cells has been associated with both tumor development and inhibition in gastric cancer. It may impact tumor development through mechanisms such as boosting cell proliferation, inducing angiogenesis, and enabling immune cell recruitment or, conversely, suppressing tumor growth via the activation of anti-tumor immune responses. The dual role of IL-17 in cancer, along with its various effects depending on the TME and immune cell composition, highlights the complexity of its activity. Current research reveals that although IL-17 might serve as a target for immunotherapy, its therapeutic potential is hindered by its various activities. Some studies have shown that anti-IL-17 drugs may be helpful, especially when paired with immune checkpoint inhibitors, whereas others point to concerns about the validity of IL-17 in gastric cancer therapy. The lack of clinical trials and the heterogeneity of human tumors underscore the necessity for individualized treatment approaches. Further studies are needed to identify the specific mechanisms of IL-17 in gastric cancer and to design targeted therapeutics appropriately.